(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this work, we examine the hyperstability of the quintic functional equation φ(u+3v)-5φ(u+2v)-φ(u-2v)+10φ(u+v)+5φ(u-v)-10φ(u)-120φ(v)=0, in Banach spaces by means of Brzdȩk’s fixed point theorem.